Modification of ZSM-5 mesoporosity and application as catalyst support in hydrodesulfurization of dibenzothiophene: Experimental and DFT studies. Issue 6 (December 2021) - Umar, Mustapha; Abdulazeez, Ismail; Tanimu, Abdulkadir; Ganiyu, Saheed A.; Alhooshani, Khalid
Abstract: The hydrodesulfurization (HDS) efficiency of NiMoS supported on modified H-ZSM-5 was investigated. The support modification was achieved via desilication (DS) in 3 – 5 M NaOH solution for 0.5 – 1 h, at 65 °C. The desilication of H-ZSM-5 increased both its mesoporosity and external surface area. The catalysts acidity and active phase formation and dispersion were influenced by the desilication of the zeolite supports. The NM/B-Z1/2 catalyst shows better HDS performance with dibenzothiophene (DBT) conversion of 87% after 4 h of reaction, while the catalyst formed from pristine ZSM-5 support (NM/Z) recorded the least DBT conversion of 38%. The DFT simulation energetics revealed that the hydrodesulfurization (HDS) process proceeded via the direct desulfurization (DDS) pathway in good correlation with the experimental findings. Extensive characterization techniques were adopted to gain insight into the physico-chemical properties of the support and the catalysts. Surface area and porosity analyzer was used for textural properties information of both the support and the catalyst. The information about surface and type of acidity, the metal-support interaction, morphology, metal charge content and dispersion of active species NiMo-S was explored by FESEM, FETEM, TPD, Pyr-FTIR, FTIR, XRD and XPS Graphical Abstract: ga1 Highlights: Desilicated ZSM-5 were used as NiMo support for HDS reaction of DBT. DFT simulations were performed to understand the reaction pathway. NM/B-Z1/2 catalyst has better catalytic properties, hence shows highest HDS activity. DFT simulation energetics revealed that the HDS proceeded via the DDS pathway.